The Role of Oxidative Stress in the Developmental Origin of Adult Hypertension - GHULMIYYAH, Labib M. (2011)
OBJECTIVE: To determine whether oxidative stress plays a role in the development of hypertension using a mouse model of fetal programming induced by endothelial nitric oxide synthase (NOS3) deficiency STUDY DESIGN: Homozygous NOS3 knockout and wild type (WT) mice were cross-bred producing maternal (NOS3(+pat/-mat)) and paternal (NOS3(+mat/-pat)) heterozygous offspring. RNA from liver and kidney tissues of female pups were obtained at 14 weeks of age. Relative expression of the heat shock protein-B6 (HspB6), Peroxiredoxin-3 (PeriRedox), superoxide dismutase-1 (SOD-1), Peroxisome proliferator-activated receptor gamma (PPAR-γ), nitric oxide synthase-1 (NOS1) and 2 (NOS2) were determined. RESULTS: In the kidneys, expression of NOS2, PeriRedox, HspB6 and SOD-1 was upregulated in NOS3(+pat/-mat) but not in NOS3(+mat/-pat) compared to WT offspring. In the liver, there were no significant differences in the expression of NOS1, NOS2, PeriRedox, SOD-1, or PPAR-γ; however, HspB6 was downregulated in both heterozygotes offspring compared with WT. CONCLUSION: The intrauterine environment alters oxidative pathways gene expression in the kidneys of offspring, which may be a mechanism in the development of adult hypertension.